Determination des periodes optimales de semis des varietes de riz a cycles court et moyen a Yangambi - Makanda, D.A.M.; Bambele, L.; Ndonda, A.; Monde, G. (2021)
Rice is the staple food for more than 2.5 billion people in developing countries with very high annual consumption exceeding in some countries 100 kg per capita. The African continent has become one of the main import poles for rice with about one quarter (1/4) of world imports because of its low production, which barely reaches 1.5% of world production. Following the agricultural calendar and in accordance with studies conducted at INERA - Yangambi on the probable periods of sowing rice in Yangambi, it appears that rice can be sown from March 15 to October 15 during the year and mainly in the wetlands of the tropics. A variety of rice, so that it can express its genetic potential, must benefit from the maximum of water and light so that one can hope for optimal yields. It is in this context that this study was conducted and with the objective of contributing to the search for the appropriate sowing dates for short and medium cycle rice varieties that would help farmers maximize their income. Depending on each sowing date, observations were made on the number of panicles per m², the number of grains per panicle, the length of the panicle, the weight of a thousand grains and the yield. The results showed that optimal planting times for rainfed rice are good when short-cycle and when rice is planted from 16 May and from 15 June for medium-cycle rice varieties. Some short and / or medium cycle varieties are favorable for sowing dates around June 29th. The benefit from this relatively late sowing of June is alluding to bird damage and so the varieties that adapt to these dates have been identified.